New Therapies for Corneal Endothelial Diseases: 2020 and Beyond. Issue 11 (15th November 2021) - Soh, Yu Qiang; Poh, Stanley S. J.; Peh, Gary S. L.; Mehta, Jodhbir S.
Abstract: Penetrating keratoplasty used to be the only surgical technique for the treatment of end-stage corneal endothelial diseases. Improvements in surgical techniques over the past decade have now firmly established endothelial keratoplasty as a safe and effective modality for the treatment of corneal endothelial diseases. However, there is a worldwide shortage of corneal tissue, with more than 50% of the world having no access to cadaveric tissue. Cell injection therapy and tissue-engineered endothelial keratoplasty may potentially offer comparable results as endothelial keratoplasty while maximizing the use of cadaveric donor corneal tissue. Descemet stripping only, Descemet membrane transplantation, and selective endothelial removal are novel therapeutic modalities that take this a step further by relying on endogenous corneal endothelial cell regeneration, instead of allogenic corneal endothelial cell transfer. Gene therapy modalities, including antisense oligonucleotides and clustered regularly interspaced short palindromic repeats–based gene editing, offer the holy grail of potentially suppressing the phenotypic expression of genetically determined corneal endothelial diseases at the asymptomatic stage. We now stand at the crossroads of exciting developments in medical technologies that will likely revolutionize the way we treat corneal endothelial diseases over the next 2 decades.